CONSUMER PERCEPTION ON DIGITAL MARKETING OF A PET FOOD IN INDONESIA - Miftahatur Rizqiyah; Muhammad Rafiq; Isma Addi Bin Jumbri (Proceeding International Conference on Information Technology and Business, 2020)
The purpose of this study was to determine the effect of consumer perceptions on digital marketing of a pet food in Indonesia. The population in this study was consumers of animal food users in Indonesia. The research sample used accidental techniques sampling with a total of 100 people. The independent variable in this study was Digital Marketing (X) and the dependent variable was Consumer Perception (Y) of purchase decisions. The method of collecting data used a questionnaire. It was a technique data collection to be done by giving a set of questions or a written statement to the respondent to answer.Keyword: Digital Marketing, Consumer Perception